Comparison of psoriasis guidelines for use of IL-23 inhibitors in the United States and United Kingdom: a critical appraisal and comprehensive review. (3rd April 2022) - Ghamrawi, R. I.; Ghiam, N.; Wu, J. J.
Abstract: Purpose: This review article aims to compare global dermatologic organizations and the clinical practice guidelines available for the use of interleukin (IL)-23 inhibitors in the treatment of psoriasis. Materials and methods: A literature review encompassing systemic therapies for the treatment of psoriasis was conducted. Guidelines from the American Academy of Dermatology (AAD)-National Psoriasis Foundation (NPF), the National Institute for Health and Care Excellence (NICE), and the British Association of Dermatologists (BAD) served as the main comparators in this review. Results: Of the American and European guidelines available for use of IL-23 inhibitors, several organizations are in agreement regarding the dosage and indications of guselkumab, tildrakizumab, and risankizumab. However, there are differences as well as insufficient recommendations concerning laboratory monitoring and screenings as well as contraindications to therapy. Conclusion: IL-23 inhibitors are safe and efficacious therapeutic options for patients with psoriasis and should be considered as a potential first-line therapy alone or in combination with topical medications, phototherapy, and other systemic non-biologic agents. Consideration should be given to the evidence-based guidelines of global dermatologic organizations to help guide therapeutic decisions.